A Comprehensive Review of Shiga Toxin-Producing Escherichia coli (STEC)Review of: Enterohemorrhagic Escherichia coli and Other Shiga Toxin-Producing E. coli; Vanessa Sperandio and Carolyn H. Hovde (ed.); (2015). ASM Press, Washington, DC. 553 pages. - Julie A. Oliver (American Society for Microbiology, 2015)
Review of: Enterohemorrhagic Escherichia coli and Other Shiga Toxin-Producing E. coli; Vanessa Sperandio and Carolyn H. Hovde (ed.); (2015). ASM Press, Washington, DC. 553 pages.